2020
DOI: 10.1002/anie.202011778
|View full text |Cite
|
Sign up to set email alerts
|

CoNi Alloy Nanoparticles Embedded in Metal–Organic Framework‐Derived Carbon for the Highly Efficient Separation of Xenon and Krypton via a Charge‐Transfer Effect

Abstract: Separation of Xe and Kr is one of the greatest challenges in the gas industries owing to their close molecular structure and similar properties. Energy‐effective adsorption‐based separation using chemically stable carbon adsorbents is a promising technology. We propose a strategy for Xe/Kr separation using MOF‐derived metallic carbon adsorbents. M‐Gallate (M=Ni, Co) were used as precursors to fabricate CoNi alloy nanoparticles embedded carbon adsorbents by one‐step auto‐reduction pyrolysis. The optimal NiCo@C‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 58 publications
3
39
0
Order By: Relevance
“…Because of the potential of the C 2 H 6 /C 2 H 4 separation, we aimed to look at even more challenging separations, such as xenon/krypton (Xe/Kr), which have small differences in chemical and physical properties. Due to the lack of dipole or quadruple moments, Xe and Kr cannot interact with porous adsorbents via intermolecular interactions, such as π–π stacking, hydrogen bonding, and dipole–dipole interactions . As a result of their similar properties (kinetic diameter: 4.0 Å for Xe and 3.7 Å for Kr; polarizability: 4.04 × 10 25 cm 3 for Xe vs. 2.48 × 10 25 cm 3 ), it remains a great challenge to achieve the efficient separation of Xe and Kr.…”
Section: Results and Discissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the potential of the C 2 H 6 /C 2 H 4 separation, we aimed to look at even more challenging separations, such as xenon/krypton (Xe/Kr), which have small differences in chemical and physical properties. Due to the lack of dipole or quadruple moments, Xe and Kr cannot interact with porous adsorbents via intermolecular interactions, such as π–π stacking, hydrogen bonding, and dipole–dipole interactions . As a result of their similar properties (kinetic diameter: 4.0 Å for Xe and 3.7 Å for Kr; polarizability: 4.04 × 10 25 cm 3 for Xe vs. 2.48 × 10 25 cm 3 ), it remains a great challenge to achieve the efficient separation of Xe and Kr.…”
Section: Results and Discissionmentioning
confidence: 99%
“…Due to the lack of dipole or quadruple moments, Xe and Kr cannot interact with porous adsorbents via intermolecular interactions, such as π−π stacking, hydrogen bonding, and dipole−dipole interactions. 49 As a result of their similar properties (kinetic diameter: 4.0 Å for Xe and 3.7 Å for Kr; polarizability: 4.04 × 10 25 cm 3 for Xe vs. 2.48 × 10 25 cm 3 ), 47 it remains a great challenge to achieve the efficient separation of Xe and Kr. A recent work demonstrated that by utilizing the difference in gate-opening pressures, flexible NbOFFIVE-2−Cu-I (ZU-62) allows for more promise in effectively separating Xe from Kr.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, strong affinities toward gas molecules can be attributed to the strongly polarized pore channels of zeolites that make regeneration a harsh process [20]. By contrast, porous carbons are considered promising adsorbents for applications in harsh industrial conditions because of their robust stability, low fabrication cost, and water resistance [3,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al obtained highly efficient Xe/Kr separation adsorbents using MOFs as precursors. The existence of the NiCo alloy in NiCo@C-700 provided higher charge-transfer performance . Non-noble Ni-based catalysts, for instance, Ni/Al 2 O 3 , Ni–MoO x /C, and Ni/boehmite, showed high conversion of LA to yield GVL but poor stability in consecutive catalytic runs due to the Ni leaching during the reaction process .…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the NiCo alloy in NiCo@C-700 provided higher charge-transfer performance. 31 Non-noble Ni-based catalysts, for instance, Ni/ Al 2 O 3 , Ni−MoO x /C, and Ni/boehmite, showed high conversion of LA to yield GVL but poor stability in consecutive catalytic runs due to the Ni leaching during the reaction process. 4 A series of Cu-based catalysts such as Cu−Cr, Cu− Fe, Cu/ZrO 2 , and Cu/SiO 2 showed excellent activity for acquiring GVL from LA; however, severe catalytic conditions for pursuing high LA conversion was needed.…”
Section: ■ Introductionmentioning
confidence: 99%